Going beyond the tip of the Drosophilidae iceberg: New Cladochaeta Coquillett, 1900 (Diptera: Drosophilidae) from Brazil - Pirani, Gabriela; Amorim, Dalton De Souza (Zootaxa, 2016)
Drosophilidae comprises more than 4,000 described species worldwide. Despite the huge number of papers published on the genus Drosophila Fallén, 1823, large parts of the family are still poorly known. The drosophiline genus Cladochaeta Coquillet, 1900 has more than 100 Neotropical and several southern Nearctic described species, but there is quite a large number of undescribed species. The Brazilian fauna of the genus was studied and 12 new species are herein described—Cladochaeta armatopsis nov. sp., C. balbiae nov. sp., C. paraitinga nov. sp., C. asapha nov. sp., C.chauliodactyla nov. sp., C. conicophallus nov. sp., C. dicrophallus nov. sp., C.grimaldii nov. sp., C. atlantica nov. sp., C. periotoi nov. sp., C. phallotrixa nov. sp. and C. stigmata nov. sp. We set the first record of C. arthrostyla Grimaldi & Nguyen, 1999 for northeastern Brazil a species otherwise known from Costa Rica, and the first record of C. bomplandi (Malloch, 1934) for the state of Minas Gerais, a species known for northeastern Argentina and southern Brazil. The descriptions include photographs for each species and detailed illustrations of the male terminalia in different views. A synopsis on the taxonomy and natural history of the genus is provided, as well as comments about the relationships of species in the genus, a discussion on problems of male terminalia sclerite homology and the problem of association between males and females.